“It’s our responsibility to make sure that we develop citizens of the future” : a thematic analysis exploring the beginnings of global consciousness in primary school children in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany Campus, New Zealand - Fuller, Victoria Louise (Massey University, 2023)
Background: Social, political, and ethical challenges such as the climate crisis, COVID-19, and the fragmentation and integration of culture and identity, are magnified by globalisation. One way to resolve these challenges is for people to advance in global consciousness (GC). Globally conscious people may express beliefs and an identity which reflect global citizenship and empathy and compassion towards others all over the world. They have a willingness and openness to engage with others who are culturally different to themselves, exhibit prosocial behaviour, show concern for global issues, and demonstrate pro- environmental attitudes and behaviours. Aim: This study explored the beginnings of GC in primary school children (aged 10 to 11) in New Zealand and how two socialising agents, parents and school, may contribute to, or act as barriers to, developing globally conscious children. Methodology: Ten semi-structured one-on-one interviews with five year six children and their five mothers, along with one semi-structured focus group with three of their year six teachers, from a high socio-economic community, were analysed using reflexive thematic analysis with a critical realist epistemology and ontology. Analysis: Three overarching themes were generated. Firstly, ‘Access to resources’, includes digital and media technology, printed media, inquiry-based learning, education addressing environmental well-being, intercultural experiences, people as experts, and financial resources that can lead to enriching experiences and opportunities. Secondly, ‘Adults as gate keepers’, argues that adults act as the gate keepers to experiences, opportunities and information which could develop globally conscious children. Lastly, ‘positive behavioural support and other-oriented mechanisms’, which refer to approaches and strategies used by both parents and schools to nurture a child’s emotional and social development. Conclusions and implications: The findings indicate that access to resources, support and scaffolding from parents and schools, and positive behavioural support approaches alongside other-oriented mechanisms, contribute to the development of characteristics and values which could further grow into GC when required. Enriching educational opportunities, experiences and interactions should be prioritised by both socialisation agents to foster these characteristics and values. This could contribute to increased cohesive collaboration on global challenges, a thriving future for humanity and a restored planet.
Keywords: 520102 Educational psychology